Pengaruh Kualitas Penyiaran dan Kemasan Program Terhadap Kepuasan Menonton Program Musik Inbox SCTV (Studi Kasus Mahasiswa BSI Pemuda Rawamangun) - Gan Gan Giantika (Jurnal Komunikasi, 2015)
The continued development of programs on television (TV) increasingly make other TV stations vying with each other in presenting the event as attractive as possible. Packaging made such a great program with the goal of engaging the penonton.Saat we are witnessing a lot of musical events are displayed in TV.Salah one event to date masik still exist in TV is a show that was broadcast live Inbox in SCTV.Untuk know whether the audience was satisfied with the event program Inbox, the authors examine this tersebut.Penelitian program using descriptive statistics with a sample size of 50 people that Student Youth Rawamangun BSI. The results showed that there are significant between Broadcasting and Packaging Quality Satisfaction Programs Watched by 88.3%, while the rest influenced by other factors not examined in this study.Keywords: Quality Broadcasting, Packaging Program, Satisfaction Watching, Music Inbox.